PAI Models: Shaping Digital-Religious Character in Vocational Schools - Wawan Setiawan; Endi Suhendi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study examines the role of Islamic Religious Education in shaping the Digital-Religious Character of Vocational High School students in Bandung amidst digital disruption and ethical degradation. Employing a comparative multi-site case study qualitative approach, this research compares two PAI implementation models: the Formal-Regulatory model at SMK Negeri 12 and the Internalization-Transcendental model at SMK Swasta Angkasa. The Formal-Regulatory model, based on government regulations and emphasizing sanctions, tends to produce temporary KDR and compliance-based adherence. Student compliance with digital communication, interaction, and content ethics is vulnerable to not being sustainable outside the school environment. Conversely, the Internalization-Transcendental model, which leverages cultural autonomy and instills the value of muraqabah (awareness of divine omnipresence) as its foundation, proves more effective in fostering intrinsic and sustainable KDR. The awareness of muraqabah strengthens students' Akidah dimension, forms Digital Self-Regulation, and integrates digital ethics as part of worship, manifested in Digital Sobriety and Tabayyun rooted in faith. This study affirms that muraqabah is a critical transversal variable determining the quality of KDR internalization. Theoretically, this study enriches the discourse on PAI, digital ethics, and transcendental character education, particularly highlighting muraqabah as a spiritual foundation for Self-Control. Practically, these findings provide contextual references for the development of value-based and spiritually grounded digital literacy strategies relevant for VHS students.